PREVALENSI HELMINTHIASIS PADA SALURAN PENCERNAAN PEDET DI PROVINSI JAWA TENGAH - Purwaningsih, .; Sumiarto, Bambang (Fakultas Peternakan Universitas Papua, 2012)
The aim of this study was to determine prevalence, and type of worm that infects the digestive tract of calves at Central Java Province. Thousand hundred thirty two of fresh faecal samples were rectally taken of 8 districts in Central Java Province. Methode of sampling is used multiple stage sampling method, proportional to the population doubles and calf each stage. Simple random sampling was done for the district, sub-district, and cluster in the farmer unit. Examinations were conducted in laboratory of parasitology Balai Besar Veteriner Wates. Methods of research carried out by using qualitative examination with natif and centrifuge method. The result of natif and centrifuge method tested positive on microscopic examination and appears the worm eggs. The results showed that the prevalence of gastrointestinal helminthiasis in calves was 41.3% and type of worm that found from the higher to lower prevalence were Strongyle sp. (24,0%), Toxocara sp. (12,5%), Trichuris sp. (6,8%), Strongyloides sp. (6,3%), Fasciola sp. (2,5%), Capillaria sp. (2,1%), dan Moniezia sp. (1,6%).